Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10763-011-9278-z
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Learning Science in Everyday Contexts: A Case Study of Everyday Science Class in Korea

Abstract: With recognition of the importance of scientific literacy for the nation and yet the increasing students' disinterest in science through school science curriculum, the Korea Science Foundation launched an innovative program called 'Everyday Science Class (ESC)' in partnership with universities and local government offices in 2003. In this work, we introduce the structure and dynamics of the ESC program in K-district through examining (1) how everyday contexts helped learners' perceptions and attitudes toward s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
(17 reference statements)
0
4
0
1
Order By: Relevance
“…This conclusion is in line with the outcomes of various studies on context-based learning approach in the literature (Demircioğlu, 2008;Gutwill-Wise, 2001;Henderleiter & Pringle, 1999;İlhan, 2010;Kesner, Hofstein & Ben-Zvi, 1997;King, Bellocchi & Ritchie, 2008;Koçak, 2012). Conclusions of studies on other disciplines other than chemistry also suggest that context-based learning positively affected students" attitudes towards the courses (Barker & Millar, 1999;Çam, 2008;Hırça, 2012;Kim, Yoon, Rae Ji & Song 2012;Ramsden, 1997;Reid, 2000;). However, there are studies in the literature, which have concluded that context-based learning activities did not have significant effects on students" attitudes towards the courses (Kutu & Sözbilir, 2011;Sari, 2010;Ünal, 2008).…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…This conclusion is in line with the outcomes of various studies on context-based learning approach in the literature (Demircioğlu, 2008;Gutwill-Wise, 2001;Henderleiter & Pringle, 1999;İlhan, 2010;Kesner, Hofstein & Ben-Zvi, 1997;King, Bellocchi & Ritchie, 2008;Koçak, 2012). Conclusions of studies on other disciplines other than chemistry also suggest that context-based learning positively affected students" attitudes towards the courses (Barker & Millar, 1999;Çam, 2008;Hırça, 2012;Kim, Yoon, Rae Ji & Song 2012;Ramsden, 1997;Reid, 2000;). However, there are studies in the literature, which have concluded that context-based learning activities did not have significant effects on students" attitudes towards the courses (Kutu & Sözbilir, 2011;Sari, 2010;Ünal, 2008).…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…These findings are consistent with relevant studies. For example, Ramsden (1997) found that courses based on contextbased approach were found to be more entertaining, Yayla (2010) found that the courses including contexts were found to be entertaining and Kim, Yoon, Ji and Song (2012) found that the contexts contributed positively to developing positive attitudes toward science learning. As a result of the research, the context-based teaching method supported by the 5E model is effective in increasing the conceptual understanding of the students and in developing positive attitudes towards the science.…”
Section: Findings Discussion and Resultsmentioning
confidence: 99%
“…Bu bulgular ilgili çalışmalarla uyumluluk göstermektedir. Örneğin Ramsden (1997), çalışmasında bağlam temelli yaklaşım ile yürütülen derslerin daha eğlenceli bulunduğunu, Yayla (2010) bağlamlar içeren dersleri öğrencilerin eğlenceli bulduğunu Kim, Yoon, Ji ve Song (2012) bağlamların fen öğrenmeye karşı olumlu tutum geliştirmeye katkı sağladığını, tespit etmişlerdir. Çalışmamızla benzer olarak Yıldırım ve Gültekin (2017), bağlamsal etkinliklerle işlenen dersleri öğrencilerin ilginç, eğlenceli ve güzel bulduğu, Ünal (2008) bağlam temelli öğretim yönteminin öğrenmede kolaylık sağladığı, İlhan (2010) bağlamların öğrenme ortamına katkı sağladığı sonuçlarına ulaşmışlardır.…”
Section: Tartişma Ve Sonuçunclassified
“…In fact, there has been a strong push in the Korean science curriculum in the last ten years to emphasize socio-scientific issues (SSI) and Science, Technology, Society and Environment (STSE) (Choi, et al, 2011;Lee, et al, 2013). Evidence of this trend is visible in the curriculum standards, textbooks, and activity guides for science teachers (Song, 2006;Ministry of Education and Human Resources, 2007;Kim, Yoon, Ji, & Song, 2012). Due to the nature of the Korean secondary schools' focus on college entrance exam preparations, fewer opportunities may exist for secondary school teachers to design lessons that incorporate content from other disciplines or even to utilize studentcentered inquiry teaching approaches in any classroom Park, Chu, & Martin, 2015).…”
Section: Teachers' Grade Levelmentioning
confidence: 99%